ANALYSIS OF RISK OF FAILURE OF LINEAR INSULATION BY EVALUATING THE CROSS-SECOND CONDUCTIVITY OF TRANSMISSIONS LINES BY DATA OF SYNCHRONIZED VECTOR MEASUREMENTS - D. A. Glukhov; E. F. Khakimzyanov; D. Ye. Titov; G. G. Ugarov; R. G. Mustafin (Известия высших учебных заведений: Проблемы энергетики)
In the article the method of an estimation of a condition of isolation of overhead transmission lines with use of the data of the synchronized vector measurements is offered, the justification of necessary diagnostic parameters is resulted.